Improved survival of locoregional-advanced larynx and hypopharynx cancer patients treated according to the DeLOS-II protocol - Wichmann, Gunnar; Wald, Theresa; Pirlich, Markus; Stoehr, Matthaeus; Zebralla, Veit; Kuhnt, Thomas; Nicolay, Nils Henrik; Hambsch, Peter; Krücken, Irene; Hoffmann, Karl-Titus; Lordick, Florian; Kluge, Regine; et al. (Frontiers in Oncology, 2024)
Introduction Larynx organ preservation (LOP) in locoregional-advanced laryngeal and hypopharyngeal squamous cell carcinoma (LA-LHSCC) being only R0-resectable (clear margins > 5 mm) by total laryngectomy (TL) is desirable. Based on tumor-specific survival (TSS) and overall survival (OS) data from the RTOG 91-11 trial and meta-analyses of randomized clinical trials (RCTs), cisplatin-based concurrent radiochemotherapy (CRT) is discussed being superior to cisplatin-based induction chemotherapy followed by radiotherapy (IC+RT) and TL followed by postoperative RT (TL+PORT) or radiochemotherapy (TL+PORCT). Outside of RCTs, T4 LHSCC treated with TL+PORCT demonstrated improved OS and TSS compared to CRT alone; comparisons with docetaxel plus cisplatin (TP)-based IC+RT are unpublished. Head-to-head comparisons in RCTs of these four alternatives are missing. Materials and methods We utilized monocentric registry data to compare the outcome in the LOP trial DeLOS-II (NCT00508664) and propensity score (PS)–matched LHSCC patients. DeLOS-II utilized endoscopic tumor staging after one cycle of TP-based IC for selecting TL+R(C)T for non-responders versus IC+RT for responders. Main risk factors for survival (localization hypopharynx, T4, N+, tobacco smoking >30 pack years, alcohol consumption >60 g/day, age, sex) were used to calculate the individual PS for each DeLOS-II patient and 330 LHSCC patients suitable for DeLOS-II according to eligibility criteria in Leipzig by CRT (78), TL+PORT (148), and TL+PORCT (104). We performed PS matching with caliper width 0.2. Results The 52 DeLOS-II patients (whole intent-to-treat cohort) and three PS-matched cohorts (52 LHSCC patients each) had equal distribution regarding risk factors including Charlson comorbidity score (CS; all p > 0.05) but differed in outcome. During 12,498.6 months of follow-up, 162 deaths (36/41/43/42 in DeLOS-II/TL+PORCT/TL+PORT/CRT, p = 0.356) occurred; DeLOS-II patients had superior OS and TSS. Compared to DeLOS-II, the HR (95% CI) observed in TL+PORCT, TL+PORT, and CRT for OS and TSS were 1.49 (0.92–2.43), 1.49 (1.15–3.18), and 1.81 (1.11–2.96) for OS; and 2.07 (0.944–4.58), 3.02 (1.32–6.89), and 3.40 (1.58–7.31) for TSS. Conclusion In addition potential LOP, LA-LHSCC suitable for LOP according the DeLOS-II protocol may achieve improved survival.